Evaluation of Sawdust and Sugarcane as Molecular Sieve in Adsorptive Concentration of Aqueous Ethanol - Taiwo, E.A.; Adeodu, O. (Ife Journal of Technology, 2011)
Availability of ethanol in its absolute form is required for its use as automobile fuel additive. Purification of aqueous ethanol by conventional distillation is energy intensive with attendant difficulty of azeotrope formation. Effectiveness of dehydration of the aqueous ethanol mixtures past the azeotropic point by adsorption using hardwood sawdust and sugarcane fibre as adsorbents was therefore investigated in this study. Batch liquid‐phase experiments were performed with both adsorbents at 10oC. Equilibrium data obtained from the experiments was fitted to Freundlich relation, Langmuir and BET correlation. Both the Langmuir and infinite form of the BET equilibrium theories were used to estimate the surface areas of the adsorbents. Sawdust preferentially adsorbed water from aqueous ethanol mixture while Sugarcane fibre relatively adsorbed ethanol from the mixtures. For the sawdust adsorbent, an improved ethanol concentration was obtained with increased concentration of ethanol in the feed as well as increased adsorbent to aqueous ethanol ratio. The experimental data fitted well into the Freundlich expression with an adsorption isotherm constant ‘n’ value of 1.3. However, BET and Langmuir gave a better fit with correlation coefficients of 0.9932 and 0.9978 respectively. Active surface area of adsorbent estimated using Langmuir and BET theories were 3.6339 x 106 and 3.3126 x 106 m2kg-1, respectively.